2021
DOI: 10.1177/2210491720983333
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of duloxetine on severity of pain and quality of life in chronic low back pain in patients who had posterior spinal fixation

Abstract: Background: In this study, we want to search the effectiveness of Duloxetine on the severity of pain and quality of life in patients with chronic low back pain who had posterior spinal fixation. Methods: In this randomized, placebo-controlled trial done in 6 months 50 patients who had CLBP and were candidates for PSF surgery selected and divided into two groups (drug and placebo). They filled the VAS, SF-36, and Hamilton questionnaires before surgery and after 6 weeks from using 30 mg of duloxetine or placebo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…When accounting for physical pain, we found the same results regarding SRC and cognitive flexibility, but also that physical pain was associated with depression, state-trait anxiety, and quality of life. Therefore, despite literature that links both SRC and physical pain with poor mental health, 3,4,14,16 cognitive impairment, 5,6 and reduced quality of life, 7,8,32,33 a more nuanced explanation would be that SRC is responsible for cognitive impairment and physical pain contributes to poor mental health and reduced quality of life. SRC and impaired cognitive flexibility have been linked before, 24,25 however, the role that physical pain has on cognitive flexibility is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When accounting for physical pain, we found the same results regarding SRC and cognitive flexibility, but also that physical pain was associated with depression, state-trait anxiety, and quality of life. Therefore, despite literature that links both SRC and physical pain with poor mental health, 3,4,14,16 cognitive impairment, 5,6 and reduced quality of life, 7,8,32,33 a more nuanced explanation would be that SRC is responsible for cognitive impairment and physical pain contributes to poor mental health and reduced quality of life. SRC and impaired cognitive flexibility have been linked before, 24,25 however, the role that physical pain has on cognitive flexibility is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, not being able to compete at a sporting level that one once could, can lead to poorer mental health and quality of life. However, even if these examples did explain reduced quality of life in athletes, it is still unclear whether this is due to SRC or physical pain, with evidence that both negatively impact quality of life, [31][32][33][34] and therefore this warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of articles identified, screened, excluded, and included are shown schematically in the PRISMA flow diagram (Figure 1). Some studies were initially found to be eligible but later excluded either due to the dose of duloxetine administered other than 60 mg [49][50][51][52] or duloxetine is assessed for subacute and chronic pain after surgery. [53][54][55] We excluded one study by Koh et al 56 because, in this trial, duloxetine 60 mg was given for 6 weeks postoperatively only in patients centrally sensitized to pain.…”
Section: Description Of Studiesmentioning
confidence: 99%